Effectiveness of Chicken Manure and Tofu Waste Liquid Organic Fertilizer on The Growth and Yield of Mustard Plants - Wahdah, Rabiatul; Ema Yunita Putri, Ade; Mulyawan, Ronny (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2025)
This research aimed to evaluate the interaction between chicken manure and tofu liquid waste-based liquid organic fertilizer (POC) on the growth and yield of pak choy, as well as to determine the individual and combined effects of chicken manure and tofu liquid waste POC on pak choy performance. The study employed a completely randomized design (CRD) with two factors. The first factor was chicken manure application: A0 (control), A1 (25 t ha⁻¹), and A2 (35 t ha⁻¹). The second factor was the concentration of tofu liquid waste POC: L0 (control), L1 (10%), L2 (15%), and L3 (20%). The experiment was conducted over three months, from February to May 2024, at the Sustainable Food Yard Demonstration Plot managed by the Palem Asri Komet Women Farmers Group. The results indicated a significant interaction between chicken manure and tofu liquid waste POC on plant height during the first and second weeks of growth. The combination of A1 (25 t ha⁻¹ chicken manure) and L1 (10% POC concentration) yielded the best results. Additionally, chicken manure alone significantly affected the number of pak choy leaves across all four weeks, with A1 again being the most effective treatment. In contrast, tofu liquid waste POC applied as a single factor did not significantly influence plant growth or yield.